Expatriates: Special Considerations in Pretravel Preparation - Pierre, Cassandra M. (Curr Infect Dis Rep, 2013)
Expatriates comprise a diverse set of travelers who face unique medical, psychiatric, and non-health-related risks as a result of increased exposure to host country environment and associated lifestyle. Expatriates have an increased risk of developing malaria, gastrointestinal disorders, latent tuberculosis, vaccine-preventable infections, and psychological disorders, when compared with other travelers, yet the majority of existing pretravel guidelines have been designed to suit the needs of nonexpatriates. Although greater interest in expatriate health issues has led to improved characterization of illness in this population, expatriate-specific risk mitigation strategies—including modifications to chemoprophylaxis recommendations, limiting tuberculosis exposure, and prevention of occupational or sexual blood-borne virus transmission—are poorly described. Occupations and destinations affect travel-related disease risk and should inform the pretravel consultation.